2022
DOI: 10.15585/mmwr.mm7148e2
|View full text |Cite
|
Sign up to set email alerts
|

Paxlovid Associated with Decreased Hospitalization Rate Among Adults with COVID-19 — United States, April–September 2022

Abstract: On November 22, 2022, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).Nirmatrelvir-ritonavir (Paxlovid), an oral antiviral treatment, is authorized for adults with mild-to-moderate COVID-19 who are at increased risk for progression to severe illness. However, real-world evidence on the benefit of Paxlovid, according to vaccination status, age group, and underlying health conditions, is limited. To examine the benefit of Paxlovid in adults aged ≥18 years in the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 9 publications
1
92
2
Order By: Relevance
“…The primary outcome was composite hospitalization or death at 28 days, which was reached in a very small proportion of patients in each group: 0.8% versus 0.8%. There are a few observational studies available evaluating either nirmatrelvir/ritonavir or molnupiravir compared to usual care, but these studies are also challenged by varying primary outcomes, low incidences of primary outcome events, or low numbers of individuals included at least 65 years or older 18 , 19 , 20 , 21 , 22 , 23 , 24 . The largest of these projects was from Shah and colleagues at the US Centers for Disease Control and Prevention 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome was composite hospitalization or death at 28 days, which was reached in a very small proportion of patients in each group: 0.8% versus 0.8%. There are a few observational studies available evaluating either nirmatrelvir/ritonavir or molnupiravir compared to usual care, but these studies are also challenged by varying primary outcomes, low incidences of primary outcome events, or low numbers of individuals included at least 65 years or older 18 , 19 , 20 , 21 , 22 , 23 , 24 . The largest of these projects was from Shah and colleagues at the US Centers for Disease Control and Prevention 24 .…”
Section: Discussionmentioning
confidence: 99%
“…There are a few observational studies available evaluating either nirmatrelvir/ritonavir or molnupiravir compared to usual care, but these studies are also challenged by varying primary outcomes, low incidences of primary outcome events, or low numbers of individuals included at least 65 years or older 18 , 19 , 20 , 21 , 22 , 23 , 24 . The largest of these projects was from Shah and colleagues at the US Centers for Disease Control and Prevention 24 . Administrative database review limited to nirmatrelvir/ritonavir patients examining effect of treatment on subsequent need of hospitalization demonstrated a a 51% lower hospitalization rate within 30 days after diagnosis than those who were not prescribed nirmatrelvir/ritonavir.…”
Section: Discussionmentioning
confidence: 99%
“…In kidney transplant recipients infected with SARS-CoV-2, the Paxlovid treatment under a strict protocol was also relatively safe and effective [ 20 ]. Another retrospective analysis also demonstrated that Paxlovid could reduce the risk of COVID-19-associated hospitalization [ 21 ]. However, these studies were not powered to demonstrate the effect of Paxlovid on the elderly patients, although they were predominantly affected by omicron surge.…”
Section: Introductionmentioning
confidence: 99%
“…S13). Further, if the true risk reduction for hospitalization of treatment is 50%, lower than the originally reported 88%, as indicated in recent CDC reports (12), universal treatment is projected to reduce mortality by 78% and hospitalization by 56% on average across all three transmission scenarios and two immune durations. Similarly, using a risk reduction for hospitalization of 30% (as seen in molnupiravir trials ( 50)) universal treatment is projected to reduce mortality by 70% and hospitalization by 41% on average across all three scenarios and two immune durations (Fig.…”
Section: Potential Risks Of Vaccine or Treatment Failurementioning
confidence: 91%